Comments On “Birth Incidence of Cerebral Palsy in Tripoli, Libya: A Population-Based Study” - Amin Bredan (Khalij-Libya Journal of Dental and Medical Research, 2021)
Dear Editor, Having read the article “Birth incidence of cerebral palsy in Tripoli, Libya: a population-based study,” published in issue 1 of volume 5 (2021) of Khalij-Libya Journal of Dental and Medical Research, I would like to express some concerns. First, the aim of the study stated at the end of the introduction is “to assess the prevalence and the most common causes for birth cerebral palsy ...” In the methods section, it states that “the study included a total of 200 patients of whom 64 were diagnosed with cerebral palsy,” without describing the inclusion and exclusion criteria for the 200 patients. But no prevalence rate based on the study is given anywhere in the main body of the paper: only the potential causes of cerebral palsy are described.